502. The Impact of Combating COVID-19 on Blood Culture Contamination and Central Line Associated Bloodstream Infection Rates. (31st December 2020) - LeRose, Jennifer; Sandhu, Avnish; Polistico, Jordan; Ellsworth, Joseph; Baran, Nancy; Cranis, Mara; Jabbo, Lavina; Cullen, Lori; Moshos, Judy; Chopra, Teena
Abstract: Background: Coronavirus disease (COVID-19) pandemic has presented challenges to every facet of the healthcare system. There is limited research evaluating the consequence of diverting resources from patient safety initiatives to COVID-19 crisis efforts. In an attempt to quantify the impact of COVID-19 on quality of patient care, we compared rates of blood culture contamination and central line associated bloodstream infections (CLABSIs) during COVID-19 to those before the pandemic. Methods: A comparative retrospective cohort study was conducted to analyze blood culture contamination and CLABSI rate per 1, 000 line days in a tertiary care hospital in Detroit within a "pre- COVID-19" timeframe, January - May 2019, and "COVID-19" timeframe, January - May 2020. The CLABSI rate data was obtained through Infection Control Surveillance System TheraDoc®. Blood culture contamination report was obtained through the Microbiology Department. Chi-square and t-test were used for statistical analysis. Results: The blood culture contamination rate increased from 3.1% during pre COVID-19 timeframe to 4.0% during COVID-19 (p-value < 0.01) (Figure 1) with the highest rate in March and April 2020 correlating with the peak of COVID-19 (Figure 2). The CLABSI rate per 1, 000 line days increased from 0.71 in pre-COVID-19 time frame to 2.70 during COVID-19 (p-value < 0.01) (Figure 1). Of the 33 CLABSIs identified during the COVID-19 time frame, 18 (54%) patients tested positive for COVID-19. When comparing COVID-19 positive and COVID-19 negative patients; average length of stay was 28.1 days shorter in the positive group (p-value < 0.01). COVID-19 positive patient had higher mortality (p-value < 0.01) (Table1). Refer to Table 1 for comparison of variables between pre COVID-19 and COVID-19 cohort and COVID-19 positive and negative cohort. Figure 1. Rate of blood culture contamination (top) and CLABSI per 1, 000 Line Days Rate (below) Between Two Study Period (Pre COVID-19 and COVID-19) Figure 2. Unique COVID Positive results in a Tertiary Care Center, Detroit, January-May 2020 Table 1. Characteristics of Entire Cohort Conclusion: A 29% increase in blood culture contamination and 280% increase in CLABSI rate represents an enormous burden on healthcare resources and decreased quality. Despite no increase in length of stay in COVID-19 positive patient, higher mortality and CLABSIs were noted in these patients. During a pandemic, healthcare systems should be allocated additional resources to accommodate the increased patient load without affecting quality of care. Disclosures: Teena Chopra, MD, MPH, Spero Therapeutics (Consultant, Advisor or Review Panel member)